The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/polym13030383
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Plasticized Sodium Ion Conducting Polymer Blend Electrolyte Membranes Based on Chitosan/Dextran Biopolymers: Ion Transport, Structural, Morphological and Potential Stability

Abstract: The polymer electrolyte system of chitosan/dextran-NaTf with various glycerol concentrations is prepared in this study. The electrical impedance spectroscopy (EIS) study shows that the addition of glycerol increases the ionic conductivity of the electrolyte at room temperature. The highest conducting plasticized electrolyte shows the maximum DC ionic conductivity of 6.10 × 10−5 S/cm. Field emission scanning electron microscopy (FESEM) is used to investigate the effect of plasticizer on film morphology. The int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 105 publications
0
19
0
Order By: Relevance
“…The electrolytes' conductivities are shown in Table 3. Based on the previous study, the conductivity of 10 −5 S cm −1 is reasonable for use in energy storage devices [11,33]. It was previously shown that the incorporation of NH 4 NO 3 (30 wt.…”
Section: Impedance Analysismentioning
confidence: 93%
See 1 more Smart Citation
“…The electrolytes' conductivities are shown in Table 3. Based on the previous study, the conductivity of 10 −5 S cm −1 is reasonable for use in energy storage devices [11,33]. It was previously shown that the incorporation of NH 4 NO 3 (30 wt.…”
Section: Impedance Analysismentioning
confidence: 93%
“…Hema et al obtained the conductivity of 10 −5 S cm −1 for the system of PVA/NH 4 Cl [10]. Asnawi et al [11] prepared a PE system of chitosan/dextran-NaTf with different glycerol concentrations. The plasticized electrolyte with the highest conductance had a maximum direct current (DC) ionic conductivity of 6.10 × 10 −5 S/cm.…”
Section: Introductionmentioning
confidence: 99%
“…To be useful, the elements in the model should have a basis in the physical electrochemistry of the system. The EEC method has been used to investigate the EIS because it is simple and shows the entire picture of the system [5,27]. The impedance diagrams in Figure 1 can generally be represented by an equivalent circuit consisting of a charge transfer resistance (R b ) in a parallel arrangement with constant phase element 1 (CPE1) in high frequency region and in a series arrangement with constant phase element 2 (CPE2) in the low frequency region, as shown in the inset of Figure 1.…”
Section: Impedance Studymentioning
confidence: 99%
“…The impedance diagrams in Figure 1 can generally be represented by an equivalent circuit consisting of a charge transfer resistance (R b ) in a parallel arrangement with constant phase element 1 (CPE1) in high frequency region and in a series arrangement with constant phase element 2 (CPE2) in the low frequency region, as shown in the inset of Figure 1. The impedance arising from CPE, ZCPE, is expressed by Equation ( 9) [5,27]…”
Section: Impedance Studymentioning
confidence: 99%
“…The bulk resistance (R b ) was calculated from the intersection of the plot with the real impedance axis, and the Z r and Z i data were shown as a Nyquist plot. The conductivity can be estimated using the equation below [35,36]:…”
Section: Electrical Impedance Spectroscopy (Eis)mentioning
confidence: 99%